Exploration of pharmacological potentialities of Bauhinia acuminata L. fruits by in vitro and in vivo assays supported by computational analysis - Protyasha Sikdar; Pritam Kundu; Fatema-Tuz- Zohora; Mst. Rehena Aktar; Bani Brota Biswas; Md. Sadman Hossain; Muaz Faruque; Khondoker Shahin Ahmed; Hemayet Hossain; Kishor Mazumder; Nripendra Nath Biswas; Samir Kumar Sadhu (Journal of Ayurveda and Integrative Medicine)
Background: In Ayurveda, Bauhinia acuminata L. had been used to treat diabetes, skin diseases, and swelling. Objective: The study was designed to assess the antidiabetic, anti-inflammatory, and antibacterial potentialities of B. acuminata fruits ethanolic extract. Phytochemical characterization by HPLC analysis, pure compound isolation by column chromatography and in silico analysis were performed. Methods: Column chromatography was conducted to isolate pure compounds. HPLC analysis was performed using sixteen standard polyphenol s. Three different methods evaluated the antidiabetic effect of the extract. Analgesic property was evaluated. Protein denaturation and formalin-induction tests were done to measure the anti-inflammatory effect. Brewer's yeast-induced pyrexia was followed to assess the antipyretic effect. Antibacterial tests were performed using disc diffusion and anti-biofilm activity assay. Binding interaction was investigated by molecular docking (MD) analysis. Moreover, oral bioavailability and toxicity profiles were analyzed using ADMET assay. Results: We have isolated β-sitosterol and β-sitosterol-3-O-β-D-glucoside from the extract. Presence of four polyphenols was evident by HPLC analysis. The extract and two isolated compounds showed prominent α-glucosidase inhibition. No mortality and abnormality were found in the acute toxicity test. The extract exhibited good peripheral analgesic and anti-inflammatory properties in a dose-dependent fashion and antipyretic effect. The extract inhibited biofilm formation on the test bacterial colony. MD analysis revealed better binding characteristics of two identified phytosterols, rutin hydrate, and kaempferol with selected protein molecules. ADMET analysis exerted compliance with the compounds except rutin with Lipinski’s rule of five. Conclusion: The assessment revealed that B. acuminata fruits extract can elicit good antidiabetic, anti-inflammatory, and antibacterial responses.